Subconjunto terminológico da CIPE® para pessoas com síndrome metabólica: base conceitual para a teoria de médio alcance do cuidado no contexto de risco cardiovascular - Félix, Nuno Damácio de Carvalho (2019)
In theory, it is stated that nursing diagnoses/outcomes and interventions support the structuring of the ICNP® Terminology Subset for people with metabolic syndrome, applicable to nursing practice directed at adults with the syndrome in Primary Health Care, allowing the induction of a middle-range theories for care in the context of cardiovascular risk. Objectives: To analyze the concepts cardiovascular risk and metabolic syndrome, identifying the respective attributes, antecedents and consequences in the context of health and Nursing; Structure a ICNP® Terminology Subset for people with metabolic syndrome in Primary Care, consisting of specialized terminology with nursing diagnoses/outcomes and interventions; Perform the clinical application of the Subset with adults with Primary Care syndrome; and Develop a mid-range theory for care in the context of cardiovascular risk from research induction and practice patterns from the structured and applied subset. Methods: This is a multiple method study, developed through the following steps: 1) Analysis of the concepts cardiovascular risk and metabolic syndrome; 2) Structuring the ICNP® Terminology Subset for people with metabolic syndrome; 3) Clinical application of the Subset with adults with Primary Care syndrome; 4) Induction of mid-range theory for care in the context of cardiovascular through research and practice. Approval was obtained from the Research Ethics Committee under protocol Nº 2.994.892. Results: After conceptual analysis, cardiovascular risk was defined as a health and care context that allows the identification of groups with risk factors for modifiable and non-modifiable cardiovascular diseases that act as early and interrelated markers of multiple etiology and heterogeneous that predisposes to the vulnerability of the individual and their collectivity. The concept of metabolic syndrome is linked as a central phenomenon of cardiovascular risk, with attributes in the context of nursing, as well as antecedents and consequences related to diagnostic criteria, lifestyle and involvement by cardiometabolic diseases. Added to the concepts analyzed, there is the specialized terminology for care directed to the person with the syndrome, composed of 389 primitive concepts, being 56.3% constant in the 2017 version of ICNP®. An operational definition of 61 nursing diagnoses/outcomes constructed through terminology was performed, and 179 nursing interventions were constructed, all subjected to content validation, in which 90% or more of the evaluators considered validated 55 diagnoses/outcomes and 169 interventions nursing staff members of the ICNP® Terminology Subset. The clinical application of the Subset with 22 adults with the syndrome in primary care was performed, and 34 diagnoses, 46 results and 110 nursing interventions were identified, mostly on psychobiological needs. The structured conceptual basis and applied in practice allowed the induction of the Theory of Care in the Context of Cardiovascular Risk (TEORISC), composed by the contextualization, purpose, assumptions and propositions, as well as the diagramming of the Theory to guide nurses in the care of individuals at cardiovascular risk, in which the metabolic syndrome is inserted as a central phenomenon. There is an unprecedented and innovative study for the context of health care and nursing to reduce morbidity and mortality from cardiovascular disease and diabetes mellitus in the medium and long term of the world population. Implications for practice and research: The potential of the products of this study to produce knowledge and care for cardiovascular risk reduction, developed by the multiprofessional team and led by nurses, using a classification system based on TEORISC. Conclusion: The study thesis is confirmed through a conceptual basis in Nursing, using a classification system with potential for insertion in health information systems and generation of indicators, to be guided and tested by a mid-range theory for to base nursing and health care in the context of cardiovascular risk.